Pendidikan Kesehatan tentang Pengetahuan Gizi Siswa di SMK - Wijayanti, Wiwit; Susanti, Rosa; Asriani, Widi Dwi; Sri, Nina (Jurnal Inovasi Pendidikan MH Thamrin, 2022)
Several problems that teenagers have health and nutrition. It is because teenagers are a group that is vulnerable to nutritional problems, teenagers are said to be vulnerable because they need energy and nutrition during their growth, development, and lifestyle changes. The purpose of this study was to describe the level of knowledge about balanced nutrition and the status of young women. This research is a descriptive study using a cross-sectional approach. The research was conducted at Vocational School (SMKN) 01 Jakarta, from October to November 2022. The sample in this study was 51 students in classes XI and XII at SMKN 01 Jakarta. The results found that 62.7% (32) students had high nutritional knowledge and 37.3% (19) students had low nutritional knowledge. Learning media prefer use to improve student’s knowledge about nutrition. Health education have an important function in nutrition education for vocational students. The recommendation of this research is that teenagers can increase their knowledge by learning media